Hubungan Pengetahuan dan Sikap dengan Kejadian Anemia Ibu Hamil di Wilayah Kerja Pustu Selemak Kabupaten Deli Serdang Tahun 2023 - Siti Aisyah; Siska Suci Triana Ginting; Mastari Mastari; Rosdiana Rosdiana (NAJ Nursing Applied Journal, 2024)
Background: Anemia is a condition in which the body has too few red blood cells (erythrocytes) which contain hemoglobin which functions to carry oxygen to all body tissues. Signs and symptoms of anemia include fatigue, weakness, decreased capacity/ability or work productivity. Anemia in pregnancy is a condition in which the mother has Hb levels below 11 gr% in the first and second trimesters or levels <10.5 gr% in the third trimester (Proverawati, 2016). Research design: The type of research used in this study is analytical with a cross-sectional approach. Cross-sectional is a research approach that emphasizes the time of measurement/observation of independent and dependent variable data only once at one time. This study was conducted to determine the relationship between one variable and another. (Notoatmodjo, 2018). Research results: showed that the characteristics of respondents according to age were mostly in the low-risk reproductive age group of 20-35 years as many as 54 people (79.4%), the rest were at-risk reproductive age <20 years>35 years as many as 14 people (20.6%). Respondents had the most formal educational backgrounds, namely Senior High School (SMA) as many as 44 people (64.7%), and at least college graduates as many as 3 people (4.4%), while Junior High School as many as 15 people (22.1%) and Elementary School as many as 6 people (8.8%). Conclusion of the study; Based on the results of the study and discussion, the author concludes: There is a relationship between the knowledge of pregnant women and the incidence of anemia with a p value of 0.015 <0.05. There is a relationship between the attitude of pregnant women and the incidence of anemia with a p value of 0.006 <0.05.